Firms and Products in International Trade: Data and Patterns for Hungary - Gábor Békés; Péter Harasztosi; Balázs Muraközy (Hungarian Academy of Sciences, Institute of Economics, 2009)
This paper provides a detailed description of Hungarian trade data and key patters drawn at the firm and product level. The IEHAS-CEFiG Hungary dataset is an almost universal panel of balance sheet information (1992-2006) merged with firmproductcountry level customs data (1992-2003) taken until the 2004 EU accession. In the Bernard et al. (2007) tradition, statistics describe the prevalence of trading activity, typology of firms by internationalisation, concentration of trade volume within and across sectors as well as geographical features of activities. The aim of this paper is both to offer background statistics to existing studies and to stimulate future research on firms and trade by offering a great deal of descriptive statistics. After describing datasets, the prevalence of trading activity across sectors, concentration of trading volume across and within sectors, spatial distribution on trade and principal trading partners are described. Stylised facts show that trading activity is heavily concentrated, both exporters and importers show better performance than non-traders, and multi-product and multi-county firms are responsible for the bulk of trade volume.
Keywords: F23; F14; D21; R12; R30; 330; international trade; exporting; firm-product level data; Internationale Wirtschaft; Export; Import; Unternehmen; Ungarn